The Effect of Price Perception and Product Quality on Purchase Decisions Mediated by Consumer Satisfaction in Malinau Regency - Sianturi, Philip Chrismanto; Hasyim, Budi; Sudarto, Sudarto; Arifin, Inang Aria; Karunia, Erick; Aswan, Aswan (Amkop Management Accounting Review (AMAR), 2025)
This study examines the relationships among price perception, product quality, consumer satisfaction, and purchasing decisions in the café industry in Malinau Regency. Using a quantitative approach, data were collected from 160 respondents who had experience purchasing products from local cafés. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test both direct and indirect relationships among variables. The results indicate that product quality and consumer satisfaction have a positive, significant effect on purchasing decisions, whereas price perception does not. However, price perception significantly affects consumer satisfaction, suggesting that consumers evaluate prices based on perceived fairness and value for money rather than as a direct trigger for purchase decisions. Furthermore, the findings reveal that consumer satisfaction plays a strategic mediating role. Consumer satisfaction mediates the relationship between price perception and purchasing decisions, as well as between product quality and purchasing decisions. This indicates that fair pricing and high product quality first enhance consumer satisfaction, which, in turn, strengthens purchasing decisions and repurchase intentions. Product quality reflected in taste, consistency, presentation, hygiene, and freshness emerges as a critical determinant of satisfaction and long-term consumer behavior in the café context. Overall, this study highlights the importance of consumer satisfaction as a key psychological mechanism linking marketing variables to purchasing decisions. The findings provide practical implications for café business owners in Malinau Regency, emphasizing the need to focus on value-based pricing strategies, consistent product quality, and positive consumption experiences to foster satisfaction and sustainable purchasing behavior. This research also contributes to the marketing literature by reinforcing the mediating role of consumer satisfaction in the food and beverage industry, particularly in semi-urban regions.